2014
DOI: 10.1371/journal.pone.0107833
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the OC Locus of Acinetobacter baumannii Genomes Predicts Extensive Structural Diversity in the Lipooligosaccharide

Abstract: Lipooligosaccharide (LOS) is a complex surface structure that is linked to many pathogenic properties of Acinetobacter baumannii. In A. baumannii, the genes responsible for the synthesis of the outer core (OC) component of the LOS are located between ilvE and aspS. The content of the OC locus is usually variable within a species, and examination of 6 complete and 227 draft A. baumannii genome sequences available in GenBank non-redundant and Whole Genome Shotgun databases revealed nine distinct new types, OCL4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(93 citation statements)
references
References 36 publications
7
84
2
Order By: Relevance
“…In any case, targeted mutagenesis and random mutagenesis of genes involved in synthesis of the LOS core oligosaccharide have shown that this component is a major contributor to Acinetobacter survival and virulence (33)(34)(35). The cluster of genes that synthesize the sugar component of LOS are extremely diverse among Acinetobacter spp., and a number of different structures have been determined or predicted (36). Modification of the LOS has also been shown to impart resistance to antimicrobials, similar to the findings for other bacterial species.…”
Section: Cell Surfacesupporting
confidence: 52%
“…In any case, targeted mutagenesis and random mutagenesis of genes involved in synthesis of the LOS core oligosaccharide have shown that this component is a major contributor to Acinetobacter survival and virulence (33)(34)(35). The cluster of genes that synthesize the sugar component of LOS are extremely diverse among Acinetobacter spp., and a number of different structures have been determined or predicted (36). Modification of the LOS has also been shown to impart resistance to antimicrobials, similar to the findings for other bacterial species.…”
Section: Cell Surfacesupporting
confidence: 52%
“…Analysis of the OC locus of strain K50 revealed that it is 98% identical to the OC locus of A. baumannii strain RBH4, classified as OCL1 (Table S4). This OC arrangement is widely distributed in CC1 and CC2 isolates and has been identified in several A. baumannii strains belonging to various sequence types, including ST158 (24). Although many of the antibiotic resistance determinants in A. baumannii are commonly organized within resistance islands (AbaR [A. baumannii resistance island]), none of the previously described AbaR regions was identified in the chromosome of strain K50.…”
Section: Sequencing and Phylogenetic And Comparative Analyses Of The mentioning
confidence: 98%
“…A. baumannii does not contain genes involved in lipopolysaccharide (LPS) O-antigen ligase activity (Kenyon and Hall, 2013;Weber et al, 2015), synthesizing instead a lipooligosaccharide (LOS) consisting of an outer core oligosaccharide (OCL) linked to Lipid A (Kenyon and Hall, 2013;Kenyon et al, 2014a); at least twelve distinct OCL structures have been inferred from genomic data (Kenyon et al, 2014b). We mapped all Thai isolates against an A. baumannii specific databases for capsular and LOS loci (KL and OCL, resp.…”
Section: Genes Associated With Capsules and Outer Corementioning
confidence: 99%